SUSTAINABLE BEVERAGE CONSUMPTION IN INDIA: EXPLORING THE CONSUMER “ATTITUDE–BEHAVIORAL INTENTION” GAP - Kumar, Pankaj; Nehra, Vikas (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the gap between consumer attitudes and behavioral intentions toward sustainable beverage consumption in India. Despite a growing awareness of environmental issues and increasing positive attitudes towards sustainable products, actual purchase and consumption behavior often fails to reflect these attitudes. By applying the Theory of Planned Behavior (TPB) and analyzing primary data collected through a structured questionnaire, this research explores the underlying causes of the attitude-behavior gap. The findings aim to provide insights for marketers and policymakers to promote sustainable consumption more effectively.